La atención al cliente y su incidencia en el fortalecimiento institucional de la asociación pesca milagrosa de la ciudad del Puyo periodo 2017-2018 - Ulicer Moises, Casco Miranda (2020)
This work was developed with the purpose of identifying how the customer service influences for the institutional strengthening of the Miraculous Fisheries Association of the city of Puyo, an Association dedicated to the provision of services, with this research work will help the improvement between the client and the company, thus a primary development will be maintained, for a stable work environment, the fundamental basis of this project was to demonstrate how customer service influences for institutional development and the achievement of objectives and goals set by the company Therefore, an observation field study was carried out. For the realization of the surveys to the external clients, and an interview guide for the internal clients, with this it could be demonstrated that the company does not provide a good customer service, therefore, neither a quality service. To carry out this research, a variety of techniques and methods were implemented, such as: surveys and an interview with internal and external clients that visit this place, such as the Miraculous Fishing Association. In this way it was possible to know the weakness and the weakest points of the association which prevents institutional development and loyalty of users, due to the importance of customer service, measures must be taken for timely sanitation, for Well-being of the company, through the results obtained will allow to establish strategies for the improvement of customer service in this way to reach the proposed goals of the association and thus meet the objectives of the company achieving the improvement of customer service will establish a customer link It will achieve a stable organizational development for internal clients and thereby improving the quality of service. Therefore, the company must implement customer service protocols, which is the cornerstone for customer loyalty, the provision of services is a highly competitive market, so the association will establish an added value to its service that distinguishes them from the competition. And consequently open an improvement in its profitability and determine an institutional strengthening, the proposed strategies are important for continuous improvement